Global Attractors for Abstract Evolutionary Equations - Naimah Aris (Department of Mathematics, Hasanuddin University, 2010)
We establish in this paper that under usual assumption on the function in abstract Cauchy problem, the existence of global attractor for the semigroup generated in this problem is merely a consequence of such a priori estimate. It is shown that asymptotic behavior of solutions can controlled by this estimate.